Race matters: cardiovascular disease risk in male US prisoners. (29th July 2021) - Miller, J; Williams, L; Alhurani, A; Saleh, Z; Bailey, A; Connell, A; Hammash, M; Chung, M; Moser, D
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIH/National Institute of Nursing Research, 1RC2NR011948 Introduction: Approximately 10% of the 2.2 million prisoners in the US have a diagnosis of cardiovascular disease (CVD) and in 2016, 28% of all deaths in custody were attributable to CVD. Black race, inadequate health literacy, and poor perceived control are predictors of increased cardiovascular disease (CVD) risk, which are prevalent in prisoners. However, little is known about the relationships among race, health literacy, and perceived control in CVD risk for male prisoners. Objective: The purpose of this study was to explore the relationships among race, health literacy, perceived control, and CVD risk while controlling for well-known risk factors (education, partner status, and body mass index) in male prisoners. Methods: We used baseline data from 349 male prisoners in a biobehavioral CVD risk reduction intervention. Health literacy was measured using the Newest Vital Sign and perceived control by the Control Attitudes Scale- Revised. CVD risk was quantified with the Framingham Risk Score (FRS). Three indirect effects of race on CVD risk were examined using serial mediation model with two sequential mediators (i.e., health literacy and perceived control) and 95% confidence intervals from 5000 bootstrap samples. Results: Of the participants (mean age = 36 + 10 years), 64.2% were white and 35.8% were black. Mean education level was 12 years and most (85.8%) were not married or partnered. Mean BMI was 28.3 + 5.0. Mean FRS was 6.63 + 4.90, indicating risk percentages of 2.3 to 13.3% over the next ten years. Black prisoners were younger (35 + 9 versus 37 + 10, p = .047) and had lower levels of health literacy (3.84 + 1.90 versus 4.69 + 1.63, p < .001) than white prisoners. No statistically significant differences in perceived control, education, partner status, or body mass index were noted between races. All three indirect effects of race on CVD were significant while the direct effect of race was not. Compared to white prisoners, black prisoners had higher levels of CVD risk through health literacy (a1b1 = .3571, 95% CI [.0948, .7162]) and lower levels of CVD risk through perceived control (a2b2 = -.1855, 95% CI [-.4388, -.0077]). Black prisoners had higher levels of CVD risk through health literacy influenced by perceived control (a1b2d21 = .0627, 95% CI [.0028, .1409]) indicating that despite the protective effect of higher levels of perceived control in black prisoners, CVD risk remained higher compared to their white counterparts. Conclusion: Future CVD risk reduction interventions in prisoners of all races, but specifically black male prisoners, should include goals of improving health literacy and perceived control in addition to the traditional modifiable risk factors often included in biobehavioral interventions.